1941
DOI: 10.1103/physrev.60.535.2
|View full text |Cite
|
Sign up to set email alerts
|

Positive Excess in Mesotron Spectrum

Abstract: Fast (Rn+Be) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1945
1945
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Moreover, if one assumes that one-half of the hard component is formed by stable particles having the same sign, one would expect a variation of the positive excess with the total number, while direct experiments showed that such an excess keeps constant between 3500 m above the sea level and the sea level. 14 In conclusion it seems that Tomonaga and…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, if one assumes that one-half of the hard component is formed by stable particles having the same sign, one would expect a variation of the positive excess with the total number, while direct experiments showed that such an excess keeps constant between 3500 m above the sea level and the sea level. 14 In conclusion it seems that Tomonaga and…”
Section: Discussionmentioning
confidence: 93%
“…Cloud chambers experiments had then shown an approximately equal number of positive and negative particles [82], but Louis Leprince-Ringuet in 1937 [83], Haydn Jones in 1939 [84], and Donald J. Hughes in 1940 [85] had found a positive excess of about 20 percent. Bernardini then proposed to "repeat the experiment of Rossi with a somewhat improved triple coincidence arrangement" (see [86], p. 536; see also [87,88]; figs. 10a-10b-10c).…”
mentioning
confidence: 99%
“…. ] under conditions when the elaborate Wilson chamber technique is impossible" (see [86], p. 536). They performed more experiments in the years 1941-1943 and published several papers (see in particular [87,86,88,89]).…”
mentioning
confidence: 99%
See 1 more Smart Citation